Experiment Investigation on Distribution of Ice Crystal During Initial Period of Frost Growth - 侯普秀; 蔡亮; 虞维平 (Zhileng xuebao)
With the picture magnifying and collecting system,ice crystal shape was observed and the picture of ice crystal at different circumstance was obtained.Then the digital image processing method was used to convert the initial picture into binary image.On the basis of analyzing this image,it is found that the distribution of ice crystal at the initial period of frost growth is different from that at fully growth period.In initial time,the maximum occupancy rate of ice crystal occurs near the cold plate,and it decreases linearly with the frost thickness.It is also found that the most important factors that influence the frost growth are the temperature of cold plate and relative humidity of air.Frost thickness and deposition of ice crystal increase with the decrease of cold plate temperature and the increase of air humidity,and the frost average density increases with the increase of air humidity.The influence of air temperature on frost growth is not obvious.